Making the most of grasslands and heathlands - Doyle McKey (Revue d'ethnoécologie)
Compared to traditional (pre-industrial) forest-based agricultural systems, traditional agriculture as practiced in grasslands and heathlands has been neglected, both by agronomists and by ethnoecologists. Examining the diversity of soil-preparation techniques used to cultivate grasslands and heathlands, and the farming systems, both past and present, in which they are enmeshed, opens up unexplored vistas in comparative agriculture. Techniques and systems that have long been studied independently—soil burning in grassland and heathland agriculture throughout the world, historical plaggen cultivation in northern European heathlands, and raised-field agriculture in present-day Africa and New Guinea and pre-Columbian South America—appear on closer inspection to be variants on a common theme. Two syntheses by Roland Portères and François Sigaut in the 1970’s, published in French and little cited by authors writing in English, furnish the foundation for a conceptual framework that links these systems and suggests new research questions. This paper updates and extends these syntheses. I show the unity and the diversity of soil-preparation techniques in grassland and heathland agriculture and propose tentative hypotheses about the ecological and social factors explaining the patterns of variation. Finally, I address the pertinence of studying these old systems for agriculture in the 21st century.